Targeted inhibition of methicillin-resistant Staphylococcus aureus biofilm formation by a graphene oxide-loaded aptamer/berberine bifunctional complex - Yi Ning; Xiaoqi Wang; Pingan Chen; Shiwu Liu; Jue Hu; Rong Xiao; Ling Li; Fangguo Lu (Taylor & Francis Group, 2022)
Biofilm formation is known to promote drug resistance in methicillin-resistant Staphylococcus aureus (MRSA), which is closely related to persistent infections in hospital settings. In this study, a DNA aptamer specific to penicillin-binding protein 2a (PBP2a) with a dissociation constant (Kd) of 82.97 ± 8.86 nM was obtained after 14 cycles of systematic evolution of ligands by exponential enrichment (SELEX). Next, a bifunctional complex containing the aptamer intercalated by berberine into the double-strand region was prepared and adsorbed onto the surface of graphene oxide (GO) by π-stacking interactions. The GO-loaded aptamer/berberine bifunctional complex showed significantly higher inhibition of MRSA biofilm formation than the control. Furthermore, this study shows that the complex possesses anti-biofilm activity, which can be attributed to the ability of the aptamer to reduce cell-surface attachment by blocking the function of PBP2a and berberine to attenuate the level of the accessory gene regulator (agr) system, which plays an important role in mediating MRSA biofilm formation. Therefore, the simultaneous delivery of berberine and PBP2a-targted aptamer using GO may have potential for the treatment of chronic infections caused by MRSA biofilms. It also provides a new avenue for multitarget treatment of bacterial biofilms.